Verbal to visual code switching improves working memory in older adults: an fMRI study - Osaka, Mariko; Otsuka, Yuki; Osaka, Naoyuki (Frontiers in Human Neuroscience, 2012)
The effects of verbal to visual code switching training on working memory performance were investigated in the elderly. Twenty-five elderly people were introduced to a verbal to visual code switching strategy (training group) while the other 25 were not (control group). During this strategy training period, participants in the training group practiced focusing their attention on a target word both by drawing the target’s figure and by forming mental images of the target. To explore the neural substrates underlying strategy effects, fMRI was used to measure brain activity of the elderly in both groups while they performed a working memory task (reading span test, RST), before and after the attention training period. RST recognition accuracy was enhanced only in the training group. fMRI data for this group showed increased activation in the anterior cingulate cortex (ACC), a region that typically shows activation in young adults performing the RST. Furthermore, activation was found both in the left and right inferior parietal lobule (IPL) and right superior parietal lobule (SPL), while there was no activation in these areas for the control group. These findings suggest that using a strategy of verbal to visual code switching helped the elderly participants to maintain the words in working memory.